Evaluation of third class survey data for national digital cadastral database population - Sarif, Abd. Sukor (2009)
The objective of Digital Cadastral Database (DCDB) introduced 'by the Department of Survey and Mapping Malaysia (DSMM) is to ease the production of land title and to facilitate the realization of e-cadastre system. The development of e-cadastre system is to change the existing method of cadastral management to fully digital system in accordance with information technology development. National Digital Cadastral Database (NDCDB) is a critical dataset in e-cadastre system. Currently, DCDB was developed based on First Class and Second Class observations. This criterion caused the Third Class survey data is left out because of the low data quality. Third Class survey data is a value of scale distance without bearing or connection line. A new methodology is needed in order to integrate Third Class survey data into DCDB. The objectives of this study are: i) to check the quality of an existing Third Class survey, and ii) to adjust the Third Class survey of the study area with acceptable accuracy. Least Square Adjustment technique was used because the measurements with differences quality can be systematically adjusted. The cadastral network was formed into several parts and the least square adjustment were carried out systematically to minimum the error propogations. Systematic summary of the adjustment results are tabulated. Locality adjustments give good results while the adjustments of inter CP's are less accurate. Results show that the existing Third Class survey is not suitable to be integrated in developing of NDCDB. Upgrading the Third Class survey Certified Plan to more accurate First Class survey is important for repopulation of NDCDB.